2000
DOI: 10.4319/lo.2000.45.7.1576
|View full text |Cite
|
Sign up to set email alerts
|

Living in suboxia: Ecology of an Arabian Sea oxygen minimum zone copepod

Abstract: Oxygen minimum zones (OMZs) are permanent suboxic features of the oceanic water column that strongly influence zooplankton distributions and biogeochemical cycles. The lower interface of prominent OMZs is characterized by a subsurface zooplankton biomass peak and high biological activity. The calanoid copepod Lucicutia grandis is an indicator species for this habitat. Its ecology in the Arabian Sea was studied during the U.S. Joint Global Ocean Flux Study (JGOFS) program to understand planktonic distributional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 67 publications
1
27
0
1
Order By: Relevance
“…The feeding strategies and behaviour of meso-and bathypelagic zooplankton differ from their epipelagic counterparts (Wishner et al 2000, Koppelmann et al 2009), so that it can be inferred that meso-, bathy-and epipelagic zooplankton communities play different roles in the carbon binding activity in these 3 ecological zones along the water column.…”
Section: Discussionmentioning
confidence: 99%
“…The feeding strategies and behaviour of meso-and bathypelagic zooplankton differ from their epipelagic counterparts (Wishner et al 2000, Koppelmann et al 2009), so that it can be inferred that meso-, bathy-and epipelagic zooplankton communities play different roles in the carbon binding activity in these 3 ecological zones along the water column.…”
Section: Discussionmentioning
confidence: 99%
“…From these field programs the lower boundaries of OMZs have been identified as particularly dynamic settings where animal densities can be remarkably high, but diversity is often low (Levin 2003). This is true of both the water column (Wishner et al 1995(Wishner et al , 1998(Wishner et al , 2000 and the seabed (Levin et al 1991, Wishner et al 1995.…”
Section: Introductionmentioning
confidence: 99%
“…However, sampling designs have yielded few autecological studies that investigate in detail the adaptations or population biology of species within OMZs. Exceptions are the detailed studies of the pelagic copepod Lucicutia grandis by Wishner et al (2000), the Humboldt squid Dosidicus gigas by Rosa & Seibel (2010), the benthic mud-ball forming cirratulid Monticellina sp. by Levin & Edesa (1997) and the spionid Paraprionospio pinnata by González & Quiñones (2000).…”
Section: Introductionmentioning
confidence: 99%
“…8c) were Lucicutia ovariformis and Scolecithricella ovata (Table 3). Lucicutia species (L. grandis) in the Arabian Sea is known to inhabit the oxygen minimum layer and is the indicator species of the layer (Gowing and Wishner, 1998;Wishner et al, 2000;Koppelmann and Weikert, 2005). Thuesen et al (1998) has reported that this is due to high lactate dehydrogenate activities in the tricarboxylic acid cycle of L. grandis under anoxic conditions, thus Lucicutia species could adapt to the oxygen minimum layer.…”
Section: -2 Community Structurementioning
confidence: 99%